Cellular catalase: structure, biogenesis, diversity, functions - Aladyeva, Tatyana L.; Zimatkin, Sergey M. (Experimental Biology and Biotechnology, 2022)
Catalase is an important antioxidant enzyme that destroys hydrogen peroxide formed in a result of normal cell metabolism, with the formation of water and oxygen, preventing lipid peroxidation of membranes and cell damage. This review analyses and summarises information about the history of discovery, structure, biogenesis, polymorphism and biological functions of cellular catalase.